Constitutional Law: Sistem Kontrol Wilayah Dengan Pembentukan Distrik Federal di Negara Rusia - Nur Rohim Yunus (ADALAH, 2022)
Having a large territory with ethnic diversity and nationalism makes the Russian Federation state must provide strategic policies, in order to regulate relations between the center and the regions. The existence of 83 Federal or State Subjects in the Russian Federation made President Vladimir Putin issued a policy in 2000 to establish 9 Federal Districts dividing federal subjects into federal districts headed by an official directly appointed by the president. This makes Russia a unique and interesting country in the analysis of constitutional law studies.